Prenomes e sobrenomes em Palotina-PR e em Maripá-PR: um estudo comparativo - Vescovi, Jessica Paula (2014)
The main goal of this work was to investigate the anthroponymic rules of two cities in the West of Paraná, Palotina and Maripá, in view of the cultural difference found in these places, considering a possible variance in the anthroponymic of each place. From the history of West, some questions were the base for this paper: is there influence of ascendance in naming? Are there similarities or diversity in the anthroponymic system? In order to answer these questions, the purpose of this work was to find similarities and differences in each place, using, as a theoretical base the West’s history (REGINATO, 1979; FREITAG, 2001; BARROS, 2002); the language system (COSERIU, 1987) and the onomastic (DICK, 1990, 1992; SEIDE, 2013a,b,c; SEIDE; SCHULTZ 2014). This work is considered a documental work, based in quantitative and qualitative analyzes, in which the data were collect in the Civil Registry of both cities, in a kind of lexicographical card. As a result of this investigation, it was noted that there convergences, related to the double names and preferred names, and divergences, associated to the surnames etymology and stability and instability in the naming of these places,